Phase and microstructural characterization of swat soapstone (Mg3Si4O10(OH)2) - Ali Sajjad; Ahmad Salar; Iqbal Asif; Ullah Rizwan; Ali Ali Hasan; Ullah Ikram; Alam Mohammad Mahtab (Reviews on Advanced Materials Science)
This study focuses on the comprehensive exploration of Swat soapstone, employing a range of analytical techniques, including X-ray diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive X-ray (EDX) spectroscopy, Fourier-transform infrared (FTIR) spectroscopy, and X-ray fluorescence (XRF) spectroscopy. XRD was used to identify the phase and lattice parameters of the soapstone. SEM further scrutinizes the dispersed soapstone particles, revealing different structural characteristics such as a slightly elongated, cubic-like structure, a straight rod-like formation, and a rough, textured surface. EDX spectroscopy was utilized for studying the elemental composition of the soapstone. The analysis identifies talc as the primary mineral in Swat soapstone, with iron, an element, also contributing notably to its composition. This underscores the complexity of Swat soapstone’s internal structure. XRF analysis further contributes to the elemental characterization, revealing a dominant composition of silicon (Si) at 48.567 wt% and a notable contribution from iron (Fe) at 16.108 wt%. FTIR analysis confirmed the absorption of infrared radiation at the non-bridging oxygen (Si–O–) within the silicate network and the Si–O–Si bending vibration. This work investigates the chemical and morphological details of the Swat soapstone.